국채선물 이론가격 결정모형 - 최영수; Choe Yeong Su; 오세진; O Se Jin; 서재영; Seo Jae Yeong (Seonmul yeongu (Online), 2004)
본 논문은 가상채권을 기초자산으로 하는 국채선물의 이론가격 산정방법으로 이자율의 변동성 추정에 적합한 I-요인 CKLS 모형에서 이항트리를 생성하여 이론가격을 산정하는 방법과 기간별 현물수익률의 상관관계를 고려하는 다요인 Vasicek 모형에서 몬테카르로 시뮬레이션을 이용하여 이론가격을 산정하는 방법을 제시하였다. 이런 방법들을 실증적으로 비교분석하기 위해 보유비용모형에 의해 한국선물거래소가 산출하는 방법과 함게 국채선물 KTB303, KTB306에 적용해본 결과, CKLS 이론가격은 한국선물거래소 산정방식 이론가격보다 거의 모든 검증구간에서 실거래가격과의 가격괴리가 매우 작음을 알 수 있고 한국선물거래소 이론가격이 만기에 무관하게 실거래가격에 근접하는 현상은 대부분의 시장참여자들이 국채선물 이론가격으로 보유비용모형에 근거하여 계산하고 있음을 알 수 있다. 다요인 Vasicek 모형의 성과가 다른 모형에 비해 저조하게 나타나는 현상은 비록 계산과정에서 음(-)의 현물이자율이 생성된 경우 이를 제외하고 다시 생성하는 과정을 했지만 최근의 저금리현상을 설명하는데 한계점이 있다고 사료되고, 또한 대부분의 시장참여자들이 이자율 기간구조를 결정하는데 중요하게 고려하는 요인은 수익률간의 상관관계가 아니라 수익률의 변동성이라는 점을 암시해 주고 있다. This paper proposes two alternative methods which are used for pricing the theoretical value of the KTB futures on the non-traded underlying asset; first method is to use the CKLS model, under which the volatility of interest rate changes is highly sensitive to the level of the interest rate, and then employ binomial trees to compute the theoretical value of futures, second one is to use the multifactor Vasicek model considering correlations between yields-to-maturity and then employ the Monte Carlo simulation to compute it. In the empirical study on KTB303 and KTB306, an CKLS methodology is superior to the conventional KORFX method based on the cost-of-carry model in terms of the size of difference between market price and theoretical price. However, the phenomena, the price discrepancy using the KOFEX methodology is very small for all test perlod, implies that the KOFEX one is being used for the most market participants. The reasons that an multifactor Vasicek methodlogy is performed poorly in comparison to another methods are 1) the Vasicek model might be not a good model for explaining the level of interest rates, or 2) the important point considered by the most market participants may be on the volatility or interest rate, not on the correlations between yields-to-maturity.